FACTORS ASSOCIATED WITH THE INCIDENCE OF TYPE 2 DIABETES MELLITUS IN WOMEN AT THE PEJUANG HEALTH CENTER BEKASI CITY IN 2023 - Maydyani, Oletha; Yoli Farradika (Perhimpunan Ahli Epidemiologi Indonesia, 2023)
Background: The 2018 Riskesdas results show that the proportion of diabetes mellitus cases in women (1.8%) is higher than the 2013 Riskesdas results (1.7%). Data obtained from the Pejuang Health Center also shows that type 2 DM cases in women are higher in 2022 with 1,661 cases compared to 2021 with 1,454 cases. Purpose: The purpose of this research was to determine factors associated with incidence of type 2 diabetes mellitus in women at the Pejuang Health Center Bekasi City in 2023. Methods: Research design used quantitative analysis with a case control approach. This research was from February to July 2023. Population in this study were women who came for screening non-communicable disease at the Pejuang Health Center. Number of samples based on the formula is 94 respondents with a sampling technique using purposive sampling. Data source from secondary data thats monthly report data Pejuang Health Center and primary data. The analysis used was univariate and bivariate analysis with Chi-Square test. Results: The results showed that there was a relationship between hypertension (p=0.007), physical activity (p=0.039), and obesity (p=0.011) with the incidence of type 2 DM in women. There was no relationship between a history of gestational diabetes mellitus (GDM) (p=0.410) and a history of giving birth to babies ≥ 4000 grams (p=1.000) with the incidence of type 2 DM in women. Conclusion: Therefore, people who are obese can start doing weekly physical activity, such as taking part in gymnastics activities held by the Pejuang Community Health Center.